Relationship of long-term prognosis to MMP and TIMP polymorphisms in patients after ST elevation myocardial infarction - Pavkova Goldbergova, Monika; Jarkovsky, Jiri; Lipkova, Jolana; Littnerova, Simona; Poloczek, Martin; Spinar, Jindrich; Kubkova, Lenka; Kluz, Krystyna; Kala, Petr; Manousek, Jan; Vasku, Anna; Parenica, Jiri (Journal of applied genetics, 2017)
The influence of polymorphisms in the large group of MMP and TIMP genes on clinical outcomes in patients after ST elevation myocardial infarction (STEMI) treated with primary PCI was analysed. In total, 550 consecutive Caucasian patients with STEMI were included in the present study, with a median of 32 months. We analysed 19 polymorphisms in the genes coding MMP and TIMP genes. The MMP-1 -519A/G and -422A/T polymorphisms are associated with combined endpoint after myocardial infarction. The hazard ratio for AT variant of MMP-1 -422A/T was 1.75 (p < 0.001); the variants with at least one A allele of MMP-1 -519A/G have less risk of combined endpoint. The TT variants of -1562C/T MMP-9 and at least one T allele of +92C/T MMP-13 were considered in a trend to affect disease progression and long-term survival after myocardial infarction. According to reclassification analysis NRI and IDI, long-term risk stratification using MMP-1 -422A/T and -519A/G polymorphisms gives additional information to the commonly used GRACE risk score. Patient stratification after myocardial infraction (MI) according to risk genotypes of MMP-1 polymorphisms could have important clinical implications for identification of patients at risk and therapeutic strategies.
Keywords: senioři; alely; infarkt myokardu s elevacemi ST úseků; ST Elevation Myocardial Infarction; Alleles; Prognosis; Middle Aged; mužské pohlaví; Matrix Metalloproteinase 13; Matrix Metalloproteinase 1; tkáňové inhibitory metaloproteinas; Adult; matrixová metaloproteinasa 13; polymorfismus genetický; Polymorphism; Tissue Inhibitor of Metalloproteinases; Matrix Metalloproteinase 9; Polymorphism, Genetic; ženské pohlaví; prognóza; Humans; matrixová metaloproteinasa 1; STEMI; koronární angioplastika; lidé středního věku; Percutaneous Coronary Intervention; TIMP; rizikové faktory; MMP; dospělí; matrixová metaloproteinasa 9; Female; Aged; Risk Factors; lidé; Male